Analyzing the efficiency of parking lots around mosque in urban area - Zhengan, Tan; Nangkula, Utaberta; Mohd Yunus, Mohd. Yazid; Ismail, Nor Atiah; Ismail, Sumarni; Mohd. Ariffin, Noor Fazamimah (INSInet Publication, 2015)
Parking facility can be considered as an important part of planning requirement of a mosque that can affect the whole development scheme, especially in urban area. The larger the town, the most likely the larger the amount of road users. this parallel occurred situation often leads to parking issues. The mosque is a sacred place for the Muslim, however, the car parking has been a long-standing issue that tarnished the image of the Mosque. These problems becomes more significant especially when mosque located around the business central such as banking, administration area and also as a center of Muslims meeting. The problem often starts with the limited numbers of parking available for people who come to mosque, and this situation turns to critical especially during Friday prayers and throughout the Ramadan month. The public complaint of insufficient car park and traffic congestion occurred in that area. This study is conducted to evaluate the efficiency of the parking spaces around urban mosque.